Thailand : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, Detailed Assessments Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2006)
The report on Thailand's Observance of Standards and Codes examines Data Module, response by the authorities, and detailed assessments using the data quality assessment framework. Thailand possesses a well-developed macroeconomic statistical system, with much strength that spans all of the datasets assessed in this report. The government clearly recognizes the importance of good statistics for effective decision making in all sectors of the economy, and it is well accepted at all levels of the statistics-producing agencies that quality builds trust and, thus, is a cornerstone of statistical work.